Time-dependent properties in two-dimensional and Hamiltonian mappings - Livorati, A. L. P.; Oliveira, J. A. de [UNESP]; Ladeira, D. G.; Leonel, E. D. [UNESP] (Springer, 2014)
Some scaling properties for chaotic orbits in a family of two-dimensional Hamiltonian mappings are studied. The phase space of the model exhibits chaos and may have mixed structure with periodic islands, chaotic seas and invariant spanning curves. Average properties of the action variable in the chaotic sea are obtained as a function of time (t). From scaling arguments, critical exponents for the ensemble average of the action variable are obtained. Scaling invariance is obtained as a function of the control parameter that controls the intensity of the nonlinearity.